2014
DOI: 10.2322/tastj.12.tn_31
|View full text |Cite
|
Sign up to set email alerts
|

Water and Food Security under Climate Change in Cambodia

Abstract: Western Cambodia is the most productive granary in the country. Since most agricultural lands are rainfed and most farmers rely only on their (non-science-based) experience, they would not adjust to changing rainfall. The Ministry of Water Resources and Meteorology of Cambodia has been working with The University of Tokyo and the Japan Aerospace Exploration Agency under the Space Application For Environment (SAFE) project since May 2012. First, we selected the most reliable general circulation models (GCMs). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Several studies on Cambodia have also been conducted. So Im et al (2014) used multimodel outputs from global atmospheric models with a combined hydrological and crop model to derive the optimum planting date in terms of minimizing the drought effect on rain-fed paddy rice production. Their results indicated that the optimum time for planting under future climate conditions was likely to be in September, approximately, 1 month later than the optimum time in the present climate.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on Cambodia have also been conducted. So Im et al (2014) used multimodel outputs from global atmospheric models with a combined hydrological and crop model to derive the optimum planting date in terms of minimizing the drought effect on rain-fed paddy rice production. Their results indicated that the optimum time for planting under future climate conditions was likely to be in September, approximately, 1 month later than the optimum time in the present climate.…”
Section: Introductionmentioning
confidence: 99%
“…With the support of DIAS, Seto et al (2013) analyzed the vertical structure of the atmospheric heating process over the Tibetan Plateau. In addition, DIAS was used to facilitate the acquisition and processing of data in a study by Monichoth et al (2014), which focused on the determination of current and estimation of future rainfall patterns, optimal planting dates, and rice yields in Cambodia. Moreover, the work of Rasmy et al (2015) in assessing future water resources in Japan and of Sawada et al (2015) on land data assimilation for the simultaneous simulation of soil moisture and vegetation dynamics were supported by DIAS data and data integration resources.…”
Section: Overview Of Dias Development Processmentioning
confidence: 99%
“…To ensure a commitment to ongoing collaboration, the AWCI and AfWCCI research communities have demonstrated the capabilities of DIAS and the benefits of its use to members of government, agencies, and academia. A number of meetings were held in which representatives of government organizations and academia were invited to present outcomes of successful implementations of DIAS as a data integration platform, e.g., the Water-Climate-Agriculture workbench in Cambodia (Monichoth et al, 2014) and the real-time flood prediction and dam operation optimization system in Japan (Shibuo et al, 2016). In addition, selected functions of DIAS were demonstrated at these events, e.g., the support system for in situ data providers to submit data, perform data quality control, and generate metadata and metadata documents compliant with ISO standards.…”
Section: Social Problem-solving Based On Data Sharing and Networkingmentioning
confidence: 99%